Membrane biodiesel production and refining technology: a critical review - Atadashi, I.M.; Aroua, Mohamed Kheireddine; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (Elsevier, 2011)
Membranes processes for the production and refining of biodiesel are being increasingly reported. Membrane technology has attracted the interest of researchers for its ability to provide high purity and quality biodiesel fuel besides its remarkable biodiesel yields. Membranes have numerous numbers of useful properties such as resistance to mechanical, chemical and thermal stress, high available surface area per unit volume, high selectivity, and ability to control the components contact between the two phases makes them potential. These properties have made them to be potential candidates for both upstream and downstream biodiesel production and refining applications. In this regards, this paper critically examined the production and refining of biodiesel fuel via membrane technology. (C) 2011 Elsevier Ltd. All rights reserved.